Endurance performance effects of hyperoxic vs. normoxic breathing during interval training in female cyclists - Nichols, J. F.; Douglas, D. W.; Buono, M. J.; McKelvey, S.; Marshall, S. (Journal of Exercise Physiology online, 1999)
The purpose of this study was to determine the differential effects on performance of hyperoxic vs. normoxic breathing during high-intensity interval training in female cyclists. Eighteen cyclists (34.9 ± 1.7 yr, VO2max 56.8± 6.5 ml·kg-1.min-1, mean± SD) were randomly assigned (single blind) to either hyperoxic (FIO2 = 40-45%) or normoxic training, which consisted of eight, 2-min maximum effort intervals with a 4-min recovery performed once per week for six weeks. Outcome variables measured pre/post training on a Lode cycle ergometer with a Vmax 29 metabolic cart were VO2max, lactate threshold (LT), leg fatigue (sec) at 110% peak power output (PPO110), peak power output (PPO), and a 2.4 km hill-climb time-trial. Group (Normoxic/Hyperoxic) by time (pre/post) repeated measures ANOVA demonstrated no significant interactions for any dependent variable, no significant main effects by group (p>0.05), and a significant main effect for time for PPO110 (p = 0.001) and PPO (p < 0.022). These data indicate that both training groups responded similarly to the training regimen. Under the conditions in this study, interval training under hyperoxic conditions produced no added benefits to performance compared to training in a normoxic state. Future studies should examine training with higher concentrations of inspired oxygen as well as greater training time while in a hyperoxic state.